The A.B.C. murders [large type] - Christie, Agatha, 1890-1976 (Christie, Agatha, 1890-1976. Hercule Poirot mysteries., 2011)
Hercule Poirot comes out of his retirement, enticed to the chase by a series of anonymous letters, each one prophesying a murder in a certain town on a certain date. He fails -- for four times -- then the net tightens. Mental deduction rather than tangible clues--Kirkus Reviews.